Política social compensatoria y justicia general (2019)
This reflection article is the result of a research project that aimed to analyze the consequences for the general justice of the way in which, currently, social policy is implemented in Colombia. In development of that policy, the State endorses the obligation to supply the basic needs of the less favored sectors through the delivery of goods and services. The hypothesis proposed is that this way of conducting social policy, when it consumes the recipient in his situation of marginality and poverty, removes him from his obligations to the social whole, which affects general justice. By virtue of this type of justice, the members of the community have the obligation to contribute to the good of the social whole, from their capacities and possibilities; if this does not happen, a form of injustice arises that has important repercussions for the construction of the social tissue.